Empowering Sustainable Education Through Differentiated Learning: A Systematic Review in Primary School - Utaminingsih, Esty Setyo; Wuriningsih, FR.; Intania, Belita Yoan; Idammatussilmi, Idammatussilmi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Differentiated learning has significant potential to address diverse learner needs and promote sustainable education, particularly in primary schools. Implementation in Indonesia, however, faces challenges such as limited teacher training, rigid curricula, and logistical constraints. The study aimed to explore the role of differentiated learning in fostering sustainable education within the Indonesian context. A systematic literature review was conducted, analyzing 97 peer-reviewed articles published between 2018 and 2024. Data were sourced from Scopus, Publish or Perish, Google Scholar, SAGE Journals, Emerald Insight, and ERIC, with findings synthesized through thematic analysis. Results showed that differentiated strategies, supported by educational technology, community-based projects, and alternative assessments, enhanced critical thinking, problem-solving, and ecological literacy. Challenges included insufficient resources and professional development, while opportunities emerged through curriculum reforms and technology integration. The study concluded that differentiated learning when effectively supported, has the potential to align primary education with sustainability principles.